2021
DOI: 10.3390/d13070295
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Investigation of Aral Wild Common Carp Populations (Cyprinus carpio) Using ddRAD Sequencing

Abstract: Common carp (Cyprinus carpio) is a widespread freshwater fish species of the Cyprinidae family, one of the largest and most diverse fish families. The natural habitats of C. carpio extend from Western Europe to South-East Asia. Common carp has remained an economically important fish species in aquaculture for many centuries and its production nowadays exceeds 4 million tons worldwide and continues to grow. The taxonomy of C. carpio is complicated, since this species is usually distinguished in two, three, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…For each pool, a target distribution of 600 to 800 nucleotide fragments was collected on a BluePippin instrument (Sage Science Inc., Beverly, MA, USA). Next, PCR was performed to enrich the libraries and to attach external unique TruSeq indices with consequent purification on AMPureXP beads [42]. The quality and concentration of the resulting libraries were checked using a Qubit 2.0 fluorometer (Invitrogen, Carlsbad, CA, USA) and a DNA Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Rad Libraries Preparation and Sequencingmentioning
confidence: 99%
“…For each pool, a target distribution of 600 to 800 nucleotide fragments was collected on a BluePippin instrument (Sage Science Inc., Beverly, MA, USA). Next, PCR was performed to enrich the libraries and to attach external unique TruSeq indices with consequent purification on AMPureXP beads [42]. The quality and concentration of the resulting libraries were checked using a Qubit 2.0 fluorometer (Invitrogen, Carlsbad, CA, USA) and a DNA Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Rad Libraries Preparation and Sequencingmentioning
confidence: 99%
“…Three articles are about taxonomy, genetics, and trophic adaptations of fishes. Genomic ddRAD-sequencing study on wild populations of common carp from the Ponto-Caspian, Balkhash-Ile, and Aral Sea basins by Shalgimbaeva et al [9] revealed that Aral Sea carp C. carpio aralensis inhabiting Balkhash-Ile and Aral Sea basins belongs to Ponto-Caspian or European carp C. carpio carpio. Authors also found several loci that can contribute to developing the population-specific, high-density SNP marker panels allowing the trade control of common carp production.…”
Section: Taxonomy Phylogeny and Evolutionmentioning
confidence: 99%